Frugivore biodiversity and complementarity in interaction networks enhance landscape‐scale seed dispersal function. (1st October 2018) - García, Daniel; Donoso, Isabel; Rodríguez‐Pérez, Javier
Abstract: Animal biodiversity matters for the provision of ecosystem functions derived from trophic activity. However, the mechanisms underlying this pattern remain elusive since animal abundance and diversity, which are the components commonly used for representing biodiversity, provide poor information about ecological complementarity in species assemblages. An approach based on species interaction networks may overcome this constraint. Here, we relate frugivore biodiversity and frugivore–plant network structure with landscape‐scale seed dispersal function. We sampled, for two years, and at fourteen plots with variable assemblages of frugivores and plants in the Cantabrian Range (N Spain), data on the abundance and diversity of frugivorous birds, the consumption of fleshy fruits of woody plants and the landscape‐scale patterns of avian seed deposition. As a measure of interaction complementarity in seed dispersal networks, we estimated the degree to which frugivore and plant species specialize in their interacting partners. Specialization varied strongly across the seed dispersal networks of the different plots, being higher in networks harbouring smaller bird species that dispersed mostly small‐fruited plants, and also in networks with late‐ripening, dominant fruiting species dispersed mostly by wintering birds. Bird abundance markedly affected seed deposition. Plots harbouring more birds received a higher density of dispersed seeds and showed higher probabilities of seed arrival and seed deposition in open microhabitats. Bird diversity also had a positive effect on the density of dispersed seed and, to a lesser extent, seed arrival probability. Independently of frugivore abundance and diversity, the density of dispersed seeds increased in plots where seed dispersal networks showed a higher degree of specialization. This study considers the structure of interaction networks to re‐address the relationship between biodiversity and ecosystem functionality, evidencing that specialization in frugivore–plant networks drives the large‐scale process of seed dispersal. These results encourage the consideration of interaction complementarity as an underlying mechanism linking animal biodiversity and trophic‐related functions. Abstract : Plain Language Summary